Analisis Kinerja Keuangan Menggunakan Metode Economic Value Added (EVA) pada PT. Astra Otoparts Tbk Tahun 2020 - 2023 - Rizkison Rizkison; Amelia Iriani; Bambang Suntoro (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
A healthy and sustainable company is the primary measure of financial performance. Approaches such as financial ratios are not sufficient to assess financial performance; methods that provide a more comprehensive picture of a company's economic value creation are also needed. Economic Value Added (EVA) is one method that can be used in performance measurement. This study aims to determine the financial performance of PT Astra Otoparts Tbk from 2020–2023 using the Economic Value Added (EVA) method, through a quantitative descriptive approach. The annual financial reports of PT Astra Otoparts Tbk from 2020 to 2023 obtained from the official website of the Indonesia Stock Exchange and the company's official website are the data used in this study. The financial performance of PT Astra Otoparts Tbk from 2020 to 2023 is considered good based on the results of the study, because the company was able to generate a positive EVA value each year, indicating that the company has succeeded in creating economic added value for shareholders and maintaining its business continuity.